Early Life Triclocarban Exposure During Lactation Affects Neonate Rat Survival. (January 2015) - Kennedy, Rebekah C. M.; Menn, Fu-Min; Healy, Laura; Fecteau, Kellie A.; Hu, Pan; Bae, Jiyoung; Gee, Nancy A.; Lasley, Bill L.; Zhao, Ling; Chen, Jiangang
Triclocarban (3, 4, 4′-trichlorocarbanilide; TCC), an antimicrobial used in bar soaps, affects endocrine function in vitro and in vivo. This study investigates whether TCC exposure during early life affects the trajectory of fetal and/or neonatal development. Sprague Dawley rats were provided control, 0.2% weight/weight (w/w), or 0.5% w/w TCC-supplemented chow through a series of 3 experiments that limited exposure to critical growth periods: gestation, gestation and lactation, or lactation only (cross-fostering) to determine the susceptible windows of exposure for developmental consequences. Reduced offspring survival occurred when offspring were exposed to TCC at concentrations of 0.2% w/w and 0.5% w/w during lactation, in which only 13% of offspring raised by 0.2% w/w TCC dams survived beyond weaning and no offspring raised by 0.5% w/w TCC dams survived to this period. In utero exposure status had no effect on survival, as all pups nursed by control dams survived regardless of their in utero exposure status. Microscopic evaluation of dam mammary tissue revealed involution to be a secondary outcome of TCC exposure rather than a primary effect of compound administration. The average concentration of TCC in the milk was almost 4 times that of the corresponding maternal serum levels. The results demonstrate that gestational TCC exposure does not affect the ability of dams to carry offspring to term but TCC exposure during lactation has adverse consequences on the survival of offspring although the mechanism of reduced survival is currently unknown. This information highlights the importance of evaluating the safety of TCC application in personal care products and the impacts during early life exposure.